Vrouwenhuis nieuws : contactblad van het Brugs vrouwenhuis. (Brugge : Vrouwenhuis, 1980)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Korte Vulderstraat 19, 8000 Brugge
Nederlands
Periodiek